Measurement of tensile bond strength of 3D printed geopolymer mortar - Panda, Biranchi (2018)
The structural capacity of construction joints in concrete bridges, deck and pavements mainly depends on the bond strength between the old substrate and new overlaid concrete. Sometimes, a mismatch in the properties of old and new concrete may lead to early age failure and shortened service life. Since in 3D concrete printing (3DCP), the whole object is made by layer by layer, bond strength is considered as one of the key parameters to ensure stability in the structure. For understanding bond mechanism, it is essential to measure bond strength at the interface between new and old layer and investigate significant parameters affecting this property. In this direction, our current work targets to analyse tensile bond strength of 3D printed geopolymer mortar with respect to printing time gap between layers, nozzle speed and nozzle standoff distance. A novel formulation of fly ash based geopolymer was made and printed using four-axis automated gantry system. Experimental findings reveal that the bond strength is a function of state of interface material between two nearby layers which can be influenced by material strength development rate and 3D printing parameters.